The Tahani fuzzy logic method for detecting violence against women in North Sumatra - Nisa, Khairun; Sari, Rina Filia (Universitas Ahmad Dahlan, 2024)
Violence against women is a pervasive issue in society. Violence often encompasses various forms, such as physical, psychological, economic, and sexual violence. This research employs the Tahani fuzzy logic method to predict cases of violence against women. The results of the analysis in query fuzzification indicate that there are 16 districts experiencing high number of cases of violence against women, namely: Asahan, Batu Bara, Dairi, Deli Serdang, Karo, Binjai, Gunung Sitoli, Pematang Siantar, Tanjung Balai, Labuhan Batu Utara, Labuhan Batu, Langkat, Padang Lawas Utara, and Simalungun. This research also provides recommendations based on detection results, utilizing the fire strength value as the highest-level ranking. Looking at the total 33 districts in North Sumatra, the highest level of violence against women is in Medan, which occurred from July to December 2022, where all four criteria for typical cases of violence against women are significantly high.